2020
DOI: 10.21608/bjas.2020.137437
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study between Hyperbaric Bupivacaine Alone Versus Fentanyl Versus Nalbuphine in Three Different Doses Intrathecally Adjuvant to Hyperbaric Bupivacaine for Lower Abdominal Surgeries

Abstract: This is a forthcoming randomized control clinical trial.We pointed tocompare between intrathecal hyperbaric bupivacaine alone versusintrathecal hyperbaric bupivacainein formation with one or the other fentanyl; or nalbuphinein 3 distinct portions (0.2 mg, 0.4mg, 0.8 mg).The study was done on 100 grown-up patients planned for elective lower stomach medical procedures under spinal sedation were randomlyallocated to 1 of the accompanying five gatherings to get intrathecally: 15 mg bupivacaine 0.5% alone (control)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
2
0
0
Order By: Relevance
“…Our results were supported by study of Makram et al, [8] as they reported that There was a statistical significance as fentanyl group (group F and group N3) was superior to groups (groups N1 andN2) and control group (group C) in spreading onset of sensory block with P-value= 0.015. Group F show rapid onset sensory blockade than group N3, but this difference was insignificant.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results were supported by study of Makram et al, [8] as they reported that There was a statistical significance as fentanyl group (group F and group N3) was superior to groups (groups N1 andN2) and control group (group C) in spreading onset of sensory block with P-value= 0.015. Group F show rapid onset sensory blockade than group N3, but this difference was insignificant.…”
Section: Discussionsupporting
confidence: 88%
“…Our results were supported by study of Makram et al, [8] as they reported that the rates of pruritis were fundamentally higher in fentanyl bunch than in nalbuphine bunches which were nil that is clarified by the counter pruritic impact of μ receptor enemies and control bunch likewise the examination was factually critical in the rate of retching and queasiness and shuddering which were higher in benchmark group and fentanyl bunch than nalbuphine gatherings.…”
Section: Discussionsupporting
confidence: 87%